The semiperiphery of academic writing discourses, communities and practices - Bennett, Karen; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
With researchers around the world are under increasing pressure to publish in high-profile international journals, this book explores some of the issues affecting authors on the semiperiphery, who often find themselves torn between conflicting academic cultures and discourses.
Keywords: Linguistics; Applied linguistics; Historical linguistics; Sociolinguistics; Discourse analysis; Language and languages -- Study and teaching